Evaluation of the disintegrant properties of native and modified forms of fonio and sweet potato starches (2016)
The effects of acid modification on the disintegrant properties of two native starches obtained from Digitaria exilis (white fonio) and Ipomea batatas (sweet potato) were evaluated in comparison with official corn starch in paracetamol tablet formulations. The starches were extracted from grains of white fonio and tubers of sweet potato, and modified by acid hydrolysis using 6% w/w hydrochloric acid for 48 h. The native and modified forms of the starches were employed as exo-disintegrants in paracetamol tablet formulations at concentrations of 2.5, 5.0, and 10.0% w/w. The disintegrant properties were assessed using crushing strength (Cs), friability (Fr), disintegration time (DT), disintegrant efficiency ratio (DER), and the dimensionless quantity DERc. The results showed that crushing strength and friability of the tablets appeared to depend on the type, concentration, and nature of disintegrant used. Disintegration time generally decreased with increase in disintegrant concentration and the values complied with the pharmacopoeial standard for uncoated tablets (_15 min). Tablets containing acid modified starches showed longer disintegration times than those containing the native starches although there were no significant differences (p>0.05) in the values. Acid modification generally increased the disintegration efficiency ratio (DER) of the formulations while the values of DERc indicated that sweet potato starch would be the most efficient disintegrant with greater ability to enhance the balance between the mechanical and disintegration properties of the tablet. Thus, the experimental starches compared well with corn starch as disintegrants and could be useful for commercial tablet formulations.